Atención sostenida y su relación con el rendimiento académico de los estudiantes de 5º de una Institución Educativa de Riohacha
The present research analyzes the relationship between sustained attention and academic performance in fifth grade students at the Eusebio Septimio Mari Educational Institution in Riohacha. The main objective was to evaluate how the ability to maintain concentration influences students' school performance. A quantitative and correlational methodology was used, with a sample of 87 students, to whom the D2 Attention Test was applied to measure sustained attention. In parallel, the grades of the first and second period of 2024 were used as an indicator of academic performance in areas key such as mathematics and natural sciences